Transatlantic Emigration and Labor Integration: Galician Women in the Buenos Aires Conurbation (1890-1960) - Farías, Ruy (Madrygal. Revista de Estudios Gallegos, 2020)
In spite of the progress made in the knowledge of the immigration from Galicia to Argentina in the last three decades, it is little what we know about the specific problems encountered by women upon their arrival, particularly in relation to their economic integration. There are important limits to what we can know about women’s economic integration by looking at the official Argentinean sources and those of the Galician associations in Argentina. I argue that the under-registration and general lack of information about women’s work should be attributed to the “domesticity discourse,” which sanctified the home as the space where women were responsible for the physical and moral reproduction of the family, while men remained the bread winners doing the productive work outside of the space of the home. My goal in this article is to start covering that gap and provide insights into women’s participation in the economy, and in particular, into their integration in the secondary sector of the economy in that area of Argentina. To that end, I use testimonies from interviews to women migrants or to their relatives living in the municipalities of Avellaneda and Lanús, Province of Buenos Aires, between 1890 and 1960. I also use marriage records from those municipalities and the Spanish Consulate’s records in Argentina.
Keywords: Galician Immigration; Argentina; 19th and 20th Centuries; Integration; Socio-Professional Inclusion; Working Women